Implementasi Legitimasi Demokrasi Dalam Hukum Pemilihan Umum (Pemilu) - Hendro Hendro; Tri Susilowati (Universitas Sains dan Teknologi Komputer, 2024)
The concept of a democratic state is implemented in general elections. General elections are a form of people's political participation in a democratic country. The implementation of direct, general, free, secret, honest and fair elections will be a reflection of the quality of democracy. This research aims to analyze the implementation of democratic legitimacy in general election law. This research was conducted using a qualitative descriptive design. An essential factor in maintaining democratic elections is through monitoring and enforcing election law. In such a context, attention needs to be paid to resolving violations appropriately and quickly. The quality of elections is also determined by the widest possible participation of the people in the process of organizing and supervising elections. Law enforcement is an effort to make the ideas of justice, legal certainty and social benefits a reality. Law enforcement is carried out through the process of real functioning of legal norms as guidelines for actors in traffic or legal relations in social and state life.